A high-performance PEO-based solid electrolyte blended with polyacrylamide and preparation method thereof

By blending polyacrylamide in PEO-based solid electrolyte and introducing bacterial cellulose as support layers, the problems of low ionic conductivity and easy growth of dendrites at room temperature of PEO-based solid electrolyte are solved, and a high-performance PEO-based solid electrolyte is achieved, suitable for high-energy density all-solid sodium metal batteries.

CN119161620BActive Publication Date: 2025-03-28NORTHWESTERN POLYTECHNICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411659537.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-28
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The PEO-based solid electrolyte has low ionic conductivity at room temperature, which cannot meet daily use needs. The concentration polarization of the negative electrode interface and the prone to growth of dendrites lead to battery failure.

Method used

By blending polyacrylamide (PAM) with PEO and introducing bacterial cellulose as a support layer, the -NH2 anchor anions and C=O of PAM promote the transfer of sodium ions and improve ionic conductivity, while ultra-thin, high mechanical strength PEO-based solid electrolyte is prepared through coating and hot pressing technology.

Benefits of technology

It significantly improves the ionic conductivity and mechanical properties of PEO-based solid electrolytes, extends the cycle life of the battery and increases the energy density, and is suitable for all-solid sodium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161620B_ABST
    Figure CN119161620B_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance PEO-based solid electrolyte blended with polyacrylamide and a preparation method, belonging to the technical field of solid electrolyte materials for sodium metal batteries. PEO with a certain ratio is mixed and stirred with NaTFSI and polyacrylamide in acetonitrile to obtain a slurry of a PEO-based solid electrolyte; a bacterial cellulose precursor liquid is vacuum filtered and then dried; the PEO slurry is coated on a bacterial cellulose support layer and dried, and the obtained film is hot pressed. Among them, the large amount of ‑NH 2 By anchoring anions, C=O promotes the transfer of sodium ions, effectively improving the ionic conductivity of the PEO-based solid electrolyte; at the same time, bacterial cellulose is introduced as a supporting layer, and a high-performance PEO-based solid electrolyte blended with polyacrylamide with ultra-thinness, high mechanical strength and high ionic conductivity is prepared through simple coating and hot pressing technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid electrolyte materials for sodium metal batteries, and particularly relates to a high-performance PEO-based solid electrolyte blended with polyacrylamide and a preparation method thereof. Background Art

[0002] Due to the non-renewable nature of fossil energy, new energy has become a top priority for people. New energy technologies are booming, and lithium batteries have been used in electric vehicles and various portable devices. However, the low abundance of lithium globally has seriously hindered its further development. For this reason, sodium, which has abundant reserves, is used to replace lithium. Sodium batteries have low production costs and are considered to be attractive next-generation energy storage devices. Sodium metal has a low reduction potential (-2.71 V), a high theoretical capacity (1166 mAh g -1 ), using sodium metal as the battery negative electrode can effectively cope with the shortage of lithium resources and is an important method to achieve high energy density.

[0003] However, sodium batteries and lithium batteries face thorny challenges. In traditional liquid electrolyte systems, liquid electrolytes can leak and burn, causing serious safety problems. Therefore, the use of solid electrolytes in combination with sodium metal negative electrodes can not only improve energy density, but also further reduce the safety hazards brought by liquid electrolytes. Among the various types of solid electrolytes, polymer solid electrolytes have the advantages of good flexibility, light weight, good compatibility with electrode interfaces, and easy processing, and have good development prospects. Among them, polyethylene oxide (PEO)-based solid electrolytes are considered to have great development prospects due to their excellent sodium salt solubility, good compatibility with the sodium metal negative electrode interface, and good roll-to-roll processing performance.

[0004] However, in PEO-based solid electrolytes, due to the + Slow diffusion along the molecular chain leads to room temperature ionic conductivity (10 -7 -10 -8), which is too low to meet daily use. At the same time, the concentration polarization at the negative electrode interface and the easy growth of dendrites cause battery failure. To this end, ionic liquids, plasticizers, inorganic filler doping, molecular blending and other methods can be used to improve ionic conductivity. At the same time, in order to inhibit the growth of dendrites and achieve high energy density of the battery, this problem is usually improved by adding a support layer to the PEO-based electrolyte. The ideal support layer should also have the characteristics of light weight, ultra-thinness, easy processing, and good compatibility with PEO. Cellulose has high mechanical strength, can effectively inhibit the growth of dendrites, and there are a large number of hydroxyl groups on the surface, which can improve its compatibility with PEO. Bacterial cellulose (BC) has the characteristics of a porous structure and is a suitable support layer to prepare an ultra-thin, high mechanical strength, and high ionic conductivity PEO-based solid electrolyte blended with polyacrylamide, thereby improving the energy density of sodium metal batteries. Summary of the invention

[0005] The purpose of the present invention is to provide a high-performance PEO-based solid electrolyte blended with polyacrylamide and a preparation method thereof, wherein polyacrylamide is used to improve the ionic conductivity of the PEO-based solid electrolyte, and ultra-thin bacterial cellulose is used as a supporting layer to prepare an ultra-thin PEO-based solid electrolyte with high mechanical strength and high ionic conductivity.

[0006] To achieve the above object, the present invention provides a method for preparing a high-performance PEO-based solid electrolyte blended with polyacrylamide, comprising the following steps:

[0007] S1, uniformly dispersing bacterial cellulose raw materials in an aqueous solution as a precursor solution;

[0008] S2, vacuum filtering the precursor solution and drying it to obtain cell cellulose;

[0009] S3, mixing a certain ratio of PEO, sodium bis(trifluoromethylsulfonyl)imide and polyacrylamide in acetonitrile to obtain a PEO-based solid electrolyte slurry;

[0010] S4, coating the PEO-based solid electrolyte slurry on the support layers on both sides of the bacterial cellulose and drying the same, using the bacterial cellulose as a BC support membrane to obtain a PEO-BC membrane;

[0011] S5. Hot-pressing the dried PEO-BC membrane to obtain a PEO-based solid electrolyte.

[0012] Preferably, in step S1, the bacterial cellulose raw material is dispersed in the aqueous solution by an ultrasonic wall-breaking machine; the power of the wall-breaking machine is 800 W; and the dispersion time is 30-60 min.

[0013] Preferably, in step S2, the drying temperature is 100° C. and the drying time is 12 hours.

[0014] Preferably, in step 3, PEO and sodium bis(trifluoromethylsulfonyl)imide are reacted according to [EO / Na + ]=15:1, the mass ratio of polyacrylamide in PEO, sodium bis(trifluoromethylsulfonyl)imide and polyacrylamide is 30%, and the stirring time is 12 hours.

[0015] Preferably, in step 4, the thickness of the BC support film is 10-15 μm, and the coating scale of the PEO-based solid electrolyte slurry is 150-250 μm; the drying process is placed at room temperature for 6 hours and then placed in a vacuum oven at 80° C. for 12-24 hours.

[0016] Preferably, in step S5, the hot pressing pressure is 45 MPa, the hot pressing temperature is 60° C., and the hot pressing time is 15-30 min.

[0017] The present invention also provides a polyacrylamide-blended high-performance PEO-based solid electrolyte prepared by the method for preparing the polyacrylamide-blended high-performance PEO-based solid electrolyte.

[0018] Therefore, the present invention adopts the above-mentioned polyacrylamide blended high-performance PEO-based solid electrolyte and preparation method, and its beneficial effects are:

[0019] 1. The present invention proposes a high-performance PEO-based solid electrolyte blended with polyacrylamide and a preparation method. Polyacrylamide (PAM) is blended with PEO. Since PAM contains a large amount of -NH2 that can anchor anions, and the C=O group can promote the transfer of sodium ions, the ionic conductivity of the PEO-based solid electrolyte is effectively improved. At the same time, bacterial cellulose is introduced as a supporting layer, and an ultra-thin, high mechanical strength, and high ionic conductivity PEO-based solid electrolyte is prepared through simple coating and hot pressing technology.

[0020] 2. The thickness of PEO-based solid electrolytes is a key factor that hinders the realization of high energy density. As a material with abundant reserves and low cost, bacterial cellulose can be used to construct the support layer of PEO-based solid electrolytes, thereby effectively reducing the thickness of the electrolyte membrane. At the same time, there are a large number of -OH groups on the surface of cellulose, which can improve its compatibility with PEO. It is an ideal support layer for PEO-based solid electrolytes, which is conducive to the high energy density of all-solid-state sodium metal batteries.

[0021] 3. The high-performance PEO-based solid electrolyte has the advantages of ultra-thinness, high mechanical strength, and high ionic conductivity, which greatly improves the mechanical and electrochemical properties, so that the assembled full battery has good rate performance and long cycle life, which is conducive to achieving high energy density of sodium batteries.

[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM images of the PEO-based solid electrolyte samples prepared in Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 1 Figure a is a SEM image of the PEO-based solid electrolyte sample prepared in Example 1. Figure 1 b is a SEM image of the PEO-based solid electrolyte sample prepared in Comparative Example 1;

[0024] Figure 2 The SEM images of the PEO-based solid electrolyte samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are shown in FIG. Figure 2 Figure a is a SEM image of the PEO-based solid electrolyte sample prepared in Example 1. Figure 2 b is a SEM image of the PEO-based solid electrolyte sample prepared in Comparative Example 1; Figure 2 Figure c is a SEM image of the PEO-based solid electrolyte sample prepared in Comparative Example 2;

[0025] Figure 3 It is a comparison diagram of stress-strain curves of the PEO-based solid electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention;

[0026] Figure 4 This is a comparison chart of the ionic conductivity of the PEO-based solid electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention;

[0027] Figure 5 It is a comparison diagram of the critical current density of the PEO-based solid electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0028] Figure 6 The graph showing the change in sodium ion migration number of the PEO-based solid electrolyte prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0029] Figure 7 It is a comparison diagram of the cycle curves of the PEO-based solid electrolyte prepared in Example 1 of the present invention and Comparative Example 1;

[0030] Figure 8 It is a comparison chart of the cycle curves of the PEO-based solid electrolyte prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0032] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0033] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0034] The present invention is further described below with reference to the accompanying drawings and specific embodiments.

[0035] The present invention provides a method for preparing a high-performance PEO-based solid electrolyte blended with polyacrylamide, which is achieved by the following steps:

[0036] Step 1, uniformly dispersing the bacterial cellulose (BC) raw material in the aqueous solution as the precursor solution; the power of the wall breaking machine is 800W; the dispersion time is 30-60 min;

[0037] Step 2: vacuum filter the obtained precursor solution and then dry it; the drying temperature is 100° C. and the time is 12 hours;

[0038] Step 3: PEO with sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) and polyacrylamide (PAM) in a certain ratio are mixed and stirred in acetonitrile to obtain a slurry of a PEO-based solid electrolyte; the ratio of PEO to NaTFSI is [EO / Na + ]=15:1, the mass proportion of PAM is 30%, and the stirring time is 12 hours;

[0039] Step 4, coating the PEO-based solid electrolyte slurry on the two-sided support layer of BC and drying to obtain a PEO-BC film; the thickness of the BC support film is 10-15 μm, and the coating scale of the PEO-based solid electrolyte slurry is 150-250 μm; the drying process is first placed at room temperature for 6 hours, and then placed in a vacuum oven and dried at 80°C for 12-24 hours;

[0040] Step 5: hot-press the dried PEO-BC membrane to obtain a PEO-based solid electrolyte; the hot-pressing pressure is 45 MPa, the hot-pressing temperature is 60° C., and the hot-pressing time is 15-30 min.

[0041] The present invention also provides a high-performance PEO-based solid electrolyte blended with polyacrylamide prepared by the above preparation method.

[0042] The following examples and comparative examples are provided for further explanation:

[0043] Example 1

[0044] This embodiment provides a method for preparing a high-performance PEO-based solid electrolyte blended with polyacrylamide:

[0045] Step 1, uniformly dispersing the bacterial cellulose (BC) raw material in the aqueous solution as the precursor solution; the power of the wall breaking machine is 800W; the dispersion time is 30min;

[0046] Step 2: vacuum filter the obtained precursor solution and then dry it; the drying temperature is 100° C. and the time is 12 hours;

[0047] Step 3, 500 mg of PEO, 230 mg of NaTFSI and 150 mg of PAM were mixed and stirred in 10 ml of acetonitrile to obtain a slurry of a PEO-based solid electrolyte; the stirring time was 12 hours;

[0048] Step 4: coating the PEO-based solid electrolyte slurry on the two-sided support layer of BC and drying to obtain a PEO-BC membrane; the thickness of the BC support membrane is 10-15 μm, and the coating scale of the PEO-based solid electrolyte slurry is 150-250 μm; the drying process is first placed at room temperature for 6 hours, and then placed in a vacuum oven and dried at 80°C for 12-24 hours;

[0049] Step 5: hot-press the dried PEO-BC membrane to obtain a PEO-based solid electrolyte, with a hot-pressing pressure of 45 MPa, a hot-pressing temperature of 60° C., and a hot-pressing time of 15-30 min.

[0050] Comparative Example 1

[0051] Step 1, 500 mg PEO, 230 mg NaTFSI and 150 mg PAM were mixed and stirred in 10 ml acetonitrile to obtain a slurry of a PEO-based solid electrolyte; the stirring time was 12 hours;

[0052] Step 2: pour the obtained PEO-based solid electrolyte slurry onto a polytetrafluoroethylene mold, dry it at room temperature for 12 hours, and dry it at 60 degrees in vacuum for 12 hours.

[0053] Comparative Example 2

[0054] Step 1, 500 mg PEO and 230 mg NaTFSI were mixed and stirred in 10 ml acetonitrile to obtain a slurry of a PEO-based solid electrolyte; the stirring time was 12 hours;

[0055] Step 2: pour the obtained PEO-based solid electrolyte slurry onto a polytetrafluoroethylene mold, dry it at room temperature for 12 hours, and dry it at 60 degrees in vacuum for 12 hours.

[0056] The morphology and performance of the samples prepared in the above examples and comparative examples were characterized, and the results are as follows:

[0057] 1. Scanning electron microscopy (SEM) characterization

[0058] Figure 1 It is a SEM cross-sectional view of the PEO-based solid electrolyte prepared in Example 1 of the present invention and Comparative Example 1. The thickness of the high-performance PEO-based solid electrolyte prepared in Example 1 is about 22 μm, which is much smaller than the PEO-based solid electrolyte sample in Comparative Example 1 with a thickness of about 145 μm.

[0059] Figure 2 It is a top view of Example 1, Comparative Example 1 and Comparative Example 2. This figure also shows that the size of the PEO-based solid electrolyte prepared in Example 1 is better.

[0060] 2. Mechanical properties test

[0061] Figure 3 : is a stress-strain curve comparison diagram of the PEO-based solid electrolyte samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. The stress-strain test was performed on the samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. The results are as follows: Figure 3 As shown, it can be observed that the mechanical properties of the PEO-based solid electrolyte prepared in Example 1 are improved by nearly two orders of magnitude compared with the samples prepared in Comparative Examples 1 and 2. The PEO-based solid electrolyte prepared in Example 1 of the present invention has good mechanical properties.

[0062] 3. Ionic conductivity test (EIS)

[0063] Figure 4 : is a comparison chart of the ionic conductivity of the samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. The samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention were tested for ionic conductivity. The results are as follows: Figure 4 As shown, it can be observed that the PEO-based solid electrolyte prepared in Example 1 has a higher ionic conductivity.

[0064] 4. Critical current density (CCD) test

[0065] Figure 5 : is a comparison chart of the critical current density of the samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. The critical current density of the PEO-based solid electrolyte prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention is tested. The results are as follows: Figure 5As shown, it can be observed that the PEO-based solid electrolyte prepared in Example 1 has a higher critical current density and a lower overpotential than the samples prepared in Comparative Examples 1 and 2, and the comprehensive performance of the PEO-based solid electrolyte in Example 1 is the best;

[0066] 5. Sodium ion migration number test (it)

[0067] Figure 6 The sodium ion migration number change diagram of the PEO-based solid electrolyte samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; the lithium ion migration number test was performed on the three samples of the present invention, and the results are as follows Figure 6 As shown; it can be observed that the PEO-based solid electrolyte prepared in Example 1 has a higher lithium ion migration number (0.62);

[0068] 6. Chemical performance test

[0069] Figure 7 It is a comparison diagram of the cycle curves of the PEO-based solid electrolyte samples prepared in Example 1 and Comparative Example 1 of the present invention; Figure 8 The figure is a comparison chart of the rate performance of the PEO-based solid electrolyte samples prepared in Example 1 of the present invention and Comparative Example 1. The PEO-based solid electrolyte samples prepared in Example 1 of the present invention and Comparative Example 1 are respectively assembled with Na3V2(PO4)3 positive electrode and sodium metal negative electrode into button batteries. The electrochemical performance of the two button batteries is tested. The results are as follows: Figure 7 , 8 As shown, the PEO-based solid electrolyte prepared in Example 1 has better cycle performance and rate performance.

[0070] It can be seen from the test results of Example 1 and Comparative Examples 1 and 2 that the high-performance PEO-based solid electrolyte blended with polyacrylamide prepared by the present invention has a thickness of about 25 μm, and has good comprehensive performance of mechanical properties, ionic conductivity and critical current density, and has a high ion migration number. The assembled battery has better cycle performance and rate performance. Combining the above advantages, the electrolyte membrane is conducive to achieving high energy density of all-solid-state sodium metal batteries.

[0071] Therefore, the present invention proposes a polyacrylamide-blended high-performance PEO-based solid electrolyte and a preparation method. Polyacrylamide (PAM) is blended with PEO. PAM contains a large amount of -NH2 that can anchor anions, and C=O can promote the transfer of sodium ions, thereby effectively improving the ionic conductivity. At the same time, bacterial cellulose is introduced as a supporting layer, and a high-performance PEO-based solid electrolyte blended with ultra-thin polyacrylamide with high mechanical strength and high ionic conductivity is prepared through simple coating and hot pressing technology.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-performance PEO-based solid electrolyte blended with polyacrylamide, characterized in that: The following steps are involved: S1, uniformly dispersing bacterial cellulose raw materials in an aqueous solution as a precursor solution; S2, vacuum filtering the precursor solution and then drying it to obtain bacterial cellulose; S3, mixing a certain ratio of PEO, sodium bis(trifluoromethylsulfonyl)imide and polyacrylamide in acetonitrile to obtain a PEO-based solid electrolyte slurry; S4, coating the PEO-based solid electrolyte slurry on the support layers on both sides of the bacterial cellulose and drying the same, using the bacterial cellulose as a BC support membrane to obtain a PEO-BC membrane; S5, hot pressing the dried PEO-BC membrane to obtain a PEO-based solid electrolyte; In step S4, the thickness of the BC support film is 10-15 μm, and the coating scale of the PEO-based solid electrolyte slurry is 150-250 μm; the drying process is placed at room temperature for 6 hours and then placed in a vacuum oven at 80° C. for 12-24 hours.

2. The method for preparing a high-performance PEO-based solid electrolyte blended with polyacrylamide according to claim 1, characterized in that: In the step S1, the bacterial cellulose raw material is dispersed in the aqueous solution by an ultrasonic wall-breaking machine; the power of the wall-breaking machine is 800W; and the dispersion time is 30-60 minutes.

3. The method for preparing a high-performance PEO-based solid electrolyte blended with polyacrylamide according to claim 1, characterized in that: In step S2, the drying temperature is 100° C. and the drying time is 12 hours.

4. The method for preparing a high-performance PEO-based solid electrolyte blended with polyacrylamide according to claim 1, characterized in that: In the step 3, PEO and sodium bis(trifluoromethylsulfonyl)imide are reacted according to [EO / Na + ]=15:1, the mass ratio of polyacrylamide in PEO, sodium bis(trifluoromethylsulfonyl)imide and polyacrylamide is 30%, and the stirring time is 12 hours.

5. The method for preparing a high-performance PEO-based solid electrolyte blended with polyacrylamide according to claim 1, characterized in that: In step S5, the hot pressing pressure is 45 MPa, the hot pressing temperature is 60° C., and the hot pressing time is 15-30 min.

6. A high-performance PEO-based solid electrolyte blended with polyacrylamide, characterized in that: The solid electrolyte is prepared by the method for preparing a polyacrylamide-blended high-performance PEO-based solid electrolyte as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Polyacrylamide (PAM) solid compound polymer electrolyte and preparation method thereof

    CN106356194A

  • Preparation method of ultrathin, light and high-mechanical-strength PEO-based solid electrolyte with cellulose membrane as supporting layer

    CN114759253A

  • Preparation method of composite solid electrolyte

    CN115000505A